Study of the active compounds and mineral elements of wormwood fruit extracts and their effect on GOT liver enzymes (Journal of the College of Basic Education, 2022)
This study was conducted on the fruit of the mature artemisia plant, which was dried and ground and taken from the western desert areas in Iraq, where the study included knowledge of the active chemical components in the artemisia plant, and where the study showed that the aqueous solution extracted (cold and hot) of the artemisia plant is of an acidic nature because it contains Many glycosidic and phenolic compounds, tannins, resins, flavonoids, alkaloids and terpenes. In addition to its ability to activate the SGOT enzyme at a ratio of (15%) for the cold aqueous extract and (48%) for the hot aqueous extract. The careful analysis of the mineral elements of the powder of the fruit of the artemisia plant proved that it contains some elements, especially (Cd, Zn, Ni, Cu, Cl, Pb) and at different concentrations, as the presence of these elements led to an increase in the process of activating the enzyme (SGOT), which plays an important role as it gives